Use of Banana Peels as Heterogeneous Catalyst for Biodiesel Production from Waste Cooking Oil - سيو براءة (Latakia University Journal -Basic Sciences Series, 2023)
Biodiesel is a clean - burning alternative diesel fuel made from bio- renewable sources such as vegetable oils and animals fats. In this paper, an economical and efficient catalyst was prepared by calcination of the waste banana peels at 500 °C, where K2O-KCl are the main components of calcined banana peels. The prepared catalyst from banana peel showed better catalytic performance compared to the lab prepared K2O/KCl in the biodiesel synthesis from waste vegetable oil. The research also included the study of the optimum conditions of the reaction. The results showed the highest yield of biodiesel 91.4% at the reaction conditions : molar ratio of oil: methanol ( 1:8 mol), the amount of catalyst (1.5 wt% of the weight of the oil), reaction temperature 65 °C over 120 minutes. The prepared biodiesel was confirmed using FTIR Spectroscopy. In addition, the physical and chemical properties of the prepared biodiesel were studied , and they confirmed the American (ASTM) and European (EN) Standards.